PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN MEDIA GAMBAR PADA MATA PELAJARAN IPA TEMA ORGAN GERAK HEWAN DAN MANUSIA KELAS V A SD NEGERI 2 NGANGANAUMALA - Wahid, Abdul (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2021)
The expected goal in this study is to improve student learning outcomes using Picture Media in the Natural Science subject with the theme of Animal and Human Movement Organs in class V A SD Negeri 2 Nganganaumala Baubau City. The subjects of the research were the fifth grade students of SD Negeri 2 Nganganaumala totaling 26 students, the details of which were 12 male students and 14 female students. The conclusions of the research are: (1) the average value of student learning outcomes is 65.77 learning completeness reaches 57.69 % or there are 15 students from 26 students who are declared complete. The results show that in the first cycle, classically students have not finished studying, obtaining a score of 65 of 57.69 %, which is smaller than the percentage of completeness desired, which is 80 %. Based on the first cycle, the results obtained that students have not reached the percentage of mastery learning, and (2) the average value of student learning outcomes is 72.31, learning mastery reaches 80.77 % or there are 21 students from 26 students who are declared complete. These results indicate that in the second cycle classically students have finished studying, students get a score of 65 which is 80.77 % greater than the desired completeness percentage, which is 80 %.